Digital breast tomosynthesis versus full-field digital mammography—Which modality provides more accurate prediction of margin status in specimen radiography?. Issue 93 (August 2017) - Amer, Heba A.; Schmitzberger, Florian; Ingold-Heppner, Barbara; Kussmaul, Julia; El Tohamy, Manal F.; Tantawy, Hazim I.; Hamm, B.; Makowski, M.; Fallenberg, Eva M.
Abstract: Objectives: To evaluate the reliability of tumor margin assessment in specimen radiography (SR) using digital breast tomosynthesis (DBT) and full-field digital mammography (FFDM) in comparison to postoperative histopathology margin status as the gold standard. Methods: After ethics committee approval, 102 consecutive patients who underwent breast conservative surgery for nonpalpable proven breast cancer were prospectively included. All patients underwent ultrasound/mammography-guided wire localization of their lesions. After excision, each specimen was marked for orientation and imaged using FFDM and DBT. Two blinded radiologists (R1, R2) independently analyzed images acquired with both modalities. Readers identified in which direction the lesion was closest to the specimen margin and to measure the margin width. Their findings were compared with the final histopathological analysis. True positive margin status was defined as a margin measuring <1 mm for invasive cancer and 5 mm for ductal carcinoma in situ (DCIS) at imaging and pathology. Results: For FFDM, correct margin direction was identified in 45 cases (44%) by R1 and in 37 cases (36%) by R2. For DBT, 69 cases (68%) were correctly identified by R1 and 70 cases (69%) by R2. Overall accuracy was 40% for FFDM and 69% for DBT; the difference was statistically significant (p < 0.0001). Sensitivity in terms of correct assessment of margin status was significantly better for DBT than FFDM (77% versus 62%). Conclusion: SR using DBT is significantly superior to FFDM regarding identification of the closest margin and sensitivity in assessment of margin status.